2016
DOI: 10.1590/0001-3765201620140613
|View full text |Cite
|
Sign up to set email alerts
|

An examination of soil and water conservation practices in the paddy fields of Guilan province, Iran

Abstract: Anais da Academia Brasileira de Ciências (2016) ABSTRACTThis study examined the use of soil and water conservation (SWC) practices among rice farmers in Iran. A random sample of 400 rice paddy farmers in the Foumanat plain of Guilan province, who use SWC measures, was drawn from a population of 52 thousand farmers. A two-part questionnaire was used to examine the level of utilization of SWC practices and to profi le paddy farmers. Internal consistency was demonstrated with a coeffi cient alpha of 0.76, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 15 publications
1
3
0
Order By: Relevance
“…Our results report that most farmers had moderately adopted SWM practices. This result is in agreement with those of previous studies in the field of soil and water conservation [67][68][69][70][71]. For all SWM categories, variations in adoption rates were observed for water audit practices, specifically with regard to using smart meters on wells and using new devices for irrigation scheduling and soil moisture monitoring.…”
Section: Discussionsupporting
confidence: 91%
“…Our results report that most farmers had moderately adopted SWM practices. This result is in agreement with those of previous studies in the field of soil and water conservation [67][68][69][70][71]. For all SWM categories, variations in adoption rates were observed for water audit practices, specifically with regard to using smart meters on wells and using new devices for irrigation scheduling and soil moisture monitoring.…”
Section: Discussionsupporting
confidence: 91%
“…Currently, Mekuriaw and Hurni (2017) finding in a related study revealed that a large percentage (87%) of farmers in Ethopian high-potential areas used physical soil and water conservation measures to keep the soil on their cultivated land and to improve yields while in lowpotential areas, nearly all farmlands in the sample that required physical soil and water structures were terraced and thus able to minimize the rate of soil erosion and improved ecosystem services. In a similar study undertaken by Ashoori et al (2016) in paddy fields of Guilan Province, Iran; finding from study revealed that a good percentage of farmers implemented agronomic soil and water conservation measures such as ratoon cropping, crop rotation, use of compost or manure and conservation tillage while a considerably lower percentage of farmers implemented physical soil and water conservation measures such as bunds and terracing etc. in the study area.…”
Section: Introductionmentioning
confidence: 93%
“…In response to these problems and to improve crop productivity, different physical and biological management practices have been introduced in different parts of Ethiopia (Mekonen and Tesfahunegn 2011). Conservation of natural resources is an essential feature of sustainable development (Ashoori et al 2016). The soils of agro-ecosystems need to be protected through the application of effective conservation measures (Lal 2020).…”
Section: Introductionmentioning
confidence: 99%